AROMATIC HYDROCARBON BIOMARKERS IN TERRESTRIAL ORGANIC MATTER OF DEVONIAN TO PERMIAN AGE - Armstroff A.; Wilkes H.; Horsfield B.; Schwarzbauer J.; Littke R. (My University, 2006)
This paper presents the results of a detailed study on the occurrence and distribution of alkylnaphthalenes and alkylphenanthrenes in 39 coal and sediment samples from the Late Palaeozoic containing predominantly terrestrial organic matter. Most of the samples represent the Euramerian flora realm and originate from locations beyond the Variscan front in Eastern, Northern and Central Europe, i.e. especially England and the Moscow Basin. The samples are of relatively low maturity (0.32 to 1.80% Rr) and consist mainly of mixtures of type III and II kerogen. Quantification of the C0- to C4-naphthalenes and the C0- to C4-phenanthrenes showed that these compound classes were highly abundant in all samples. Aromatic hydrocarbon maturity parameters in general are in good agreement with measured vitrinite reflectance values. 1,2,7-Trimethylnaphthalene, an assumed diagenetic product of oleanane type biomarkers was present in all investigated samples. This observation provides evidence that oleanane type lipids were biosynthesised by organisms predating the evolution of angiosperms or that assumed formation pathways for 1,2,7-trimethylnaphthalene are insecure. 1,2,8-Trimethylphenanthrene was significantly enriched in samples from the Permian and the one sample from the Devonian investigated in this study. The precursor(s) of 1,2,8-trimethylphenanthrene therefore may have been produced by organisms which were least abundant in the Carboniferous depositional environments represented by our samples. © 2006 Elsevier B.V. All rights reserved.
Keywords: AGE AND SOURCE RELATIONSHIP; ALKYLNAPHTHALENES; ALKYLPHENANTHRENES; AROMATIC BIOMARKERS; LATE PALAEOZOIC; TERRESTRIAL ORGANIC MATTER; Permian; Carboniferous; Devonian; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская